Microwave-assisted solvothermal synthesis of In-MIL-68 derived hollow In2O3 microrods for enhanced 1-pentanol sensing performance - de Sá, Bruna S. [UNESP]; Perfecto, Tarcísio M.; de Oliveira, Davi S. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2023)
The development of microbial volatile organic compounds (MVOCs) sensors is helpful due to the detection of toxic contaminants in foods, non-invasive disease diagnosis, and monitoring of contamination in industrial processes. Materials that are typically applied in the sensors field are semiconductor metal oxides (SMOx) since they have shown efficiency in identifying gases. Using metal-organic frameworks (MOFs) as precursors is an exciting approach to producing well-structured SMOx. Therefore, we report the preparation and characterization of In-MIL-68 (a MOF composed of terephthalic acid) derived hollow In2O3 microrods. The sensor material was obtained by the microwave-assisted solvothermal (MAS) method and subsequent calcination. We also show the application of the hollow In2O3 microrods as a 1-pentanol sensor for the first time. The sensor demonstrated exceptional sensitivity to this MVOC compared to other sensors reported in the literature, achieving a great response of 390 for 100 ppm of this compound at 350 °C.
Keywords: Gas sensor; Indium oxide; Metal-organic framework; Microbial volatile organic compounds; Microorganisms; Microwave-assisted solvothermal synthesis